The Key to Biblical Studies in Chinese Academia: A Review of Professor Tian Haihua’s New Work, The History and Methodology of Biblical Interpretation - LIN , Yan (Journal of Research for Christianity in China (JRCC), 2025)
The History and Methodology of Biblical Interpretation traces the historical development of biblical exegesis, dividing its history into the following periods: Medieval Jewish-Christian exegesis, Renaissance, Reformation, Enlightenment-era biblical interpretation and translation, modern historical-critical biblical studies, social science approaches to biblical interpretation, feminist biblical interpretation, postcolonial biblical criticism, and postmodern biblical interpretation. Spanning over three millennia, it is a veritable historical epic. Each chapter focuses on three representative exegetes or intellectual currents, employing a horizontal analysis that effectively integrates diachronic and synchronic research. A key feature of this book is its clarification of the sequential or relative relationships among scholars and schools of thought, offering readers a clear presentation of the academic lineage of Western biblical hermeneutics and the image of the scholarly community collectively constructed by these scholars. Simultaneously, the book integrates theory with methodology; in the interpretive process, abstract theories are translated into concrete methods. Through accessible yet profound analysis, it ultimately presents a rich array of hermeneutical achievements.